The Impact of Human-AI Collaboration on Employee Performance in Digital Companies - Leutrim Mert (IHSA Institute, 2025)
The rapid adoption of Artificial Intelligence (AI) technologies has transformed the operations of digital companies and created new forms of collaboration between employees and AI systems. Human-AI Collaboration has emerged as a strategic approach that combines human creativity, judgment, and adaptability with AI-driven analytics, automation, and decision support capabilities. This study aims to analyze the impact of Human-AI Collaboration on employee performance in digital companies. A quantitative research approach was employed using a cross-sectional survey method involving 286 employees who actively use AI tools in software companies, FinTech firms, e-commerce businesses, and digital marketing agencies. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that Human-AI Collaboration has a positive and significant effect on employee performance. Specifically, trust in AI, AI usability, and AI reliability were found to be significant determinants of effective collaboration, contributing to higher productivity, improved work quality, greater efficiency, and better decision-making outcomes. These findings suggest that digital organizations should invest in AI literacy, transparent AI governance, and employee-centered AI integration strategies. Future AI implementation should emphasize collaborative intelligence that enhances, rather than replaces, human capabilities.